Teaching at The Right Level sebagai Wujud Pemikiran Ki Hadjar Dewantara di Era Paradigma Baru Pendidikan - Faradila, Anisa; Priantari, Ika; Qamariyah, Farizatul (Jurnal Pendidikan Non formal, 2023)
Ki Hadjar Dewantara, a descendant of the aristocracy of the Yogyakarta Palace, with a profound concern for education, has given rise to a philosophical concept of National Education. According to Ki Hadjar Dewantara, education is a process of guiding every inherent potential in each student to achieve the highest level of well-being and happiness as part of society. Education, as a guidance in the growth of a child's life, reflects Ki Hadjar Dewantara's belief that every development of a student is something beyond the control or will of a teacher. Just as National Education, based on Ki Hadjar Dewantara's thoughts, the government is currently constructing a new paradigm of education that is flexible for teachers in creating classroom learning through the Teaching at The Right Level (TaRL) approach. The alignment of the flexible characteristics in the new paradigm of education with the philosophical education of Ki Hadjar Dewantara is a new hope in the development of education in Indonesia. To determine the compatibility of the concept of the new education paradigm with the implementation in the field, it is necessary to further examine the alignment of Ki Hadjar Dewantara's thoughts with the implementation of TaRL in the new education paradigm. This study employs literature review research. The results show that there is alignment between the philosophical thinking of Ki Hadjar Dewantara and the implementation of TaRL in the new education paradigm at the Senior High School level. Based on this literature review research, it can be concluded that the implementation of TaRL in schools can be considered as a manifestation of Ki Hadjar Dewantara's thoughts.